MONITORING THE EFFECTIVENESS OF EDUCATION IN THE EDUCATION MODERNIZATION AND COMPUTERIZATION - Beloglazov, A.A.; Beloglazova, L.B.; Bondareva O.B., O.B.; Ismailova, H.E. (Vestnik Rossiĭskogo universiteta druzhby narodov. Serii͡a︡ Informatizat͡s︡ii͡a︡ obrazovanii͡a, 2017)
Article devoted to the capabilities of computer testing in the diagnosis of the results of the educational process. The paper provides a rationale for the relevance and timeliness of the application of this technique in connection with the trends of contemporary social development - computerization and setevizatsiey society. Also attention is paid to the formation of the transformations, which lead to a digital communication technology and, in particular, the Internet. Specifies that the computer testing in a modern two-level university education should be tailored to the received in high school competency approach. A possible variant of use of computer-based testing to assess the results of training students in the discipline “philosophy”. The conclusion about the effectiveness of computer-based testing in the monitoring of education in the modernization and computerization of modern education.